TINJAUN HUKUM ISLAM TERHADAP PENERAPAN JANGKA WAKTU WAKAF MENURUT PASAL 6 UNDANG-UNDANG NOMOR 41 TAHUN 2004 - Nur Hidayah (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to analyze the Arrangement of Term Waqf according to Article 6 of Law Number 41 of 2004 concerning Waqf. The results of this study indicate that Islamic Law on the Application of the Term of Waqf according to Article 6 of Law Number 41 of 2004 concerning Waqf is something that is very helpful in distributing some assets in the form of movable and immovable assets to be used as benefit and with the existence of term waqf. time expands the space in distributing part of the assets with a period of time agreed upon by the wakif and the recipient.